An Investigation into the Causes of Failures in Railway Infrastructure at Transnet Freight Rail - A Case of the Steel and Cement Business Unit - Ramuhulu, Mpho; Chiranga, Ngonidzashe (International Journal of Sustainable Development & World Policy, 2018)
The purpose of the study was to investigate the causes of railway infrastructure failures in the case of Transnet Freight Rail’s Steel and Cement business unit and suggest methods to increase the reliability of the business unit’s railway infrastructure and recommend policies to increase the reliability of the railway infrastructure., A reliable railway infrastructure will grow the market share of the business unit, reduce operating costs, grow the economy of South Africa, create employment, and increase the revenue of the business unit. A quantitative approach was used to conduct the research and questionnaires were distributed to a population of 1048 employees that work for the business unit with the participants chosen based on their railway infrastructure experience and railway exposure. The study revealed that extreme weather conditions, ageing railway infrastructure, vegetation, lack of maintenance, other Transnet departments, poor railway infrastructure maintenance, theft and vandalism, are the major causes of railway infrastructure failures in the business unit. The research made a number of recommendations including that the business unit develop a lifecycle management program for its ageing infrastructure and introduce skills transfer programs in place. Railway maintenance was suggested as being a key performance measure.